Phosphorylation of sago (Metroxylon sagu) starch cross-linked with sodium triphosphate and the physicochemical properties of the potential application in batter - Seet, Chi Yau; Abd Razak, Hanisah Kamilah; Yusoff, Nor Shariffa; Abdullah, Uthumporn Utra @ Sapina (Wiley-Blackwell, 2021)
This study evaluated the effect of sago starch cross-linked phosphorylated with sodium tripolyphosphate (STPP) (4%, 8%, and 12%) in fried batter. The 12% STPP produced cross-linked starch with the highest degree of substitution (DS) at 0.017. The swelling power, amylose content, peak viscosity, breakdown viscosity, and setback were reduced as the concentration of STPP increased. The oil uptake of the fried batter added with 20% of cross-linked sago starch with the highest DS (WFCLS12) was significantly reduced from 29.16% to 19.5%. The fracturability of the fried batter added with cross-linked sago starch showed significantly higher crispness (WFCLS4—883.45 g; WFCLS8—666.61 g; WFCLS12—499.89 g) than 100% wheat flour (WF—1094.60 g). It was demonstrated that STPP (especially WFCLS12) is an effective cross-linking agent, and the addition of cross-linked sago starch into wheat flour–based batter significantly (p < .05) improved the quality of the batter.